APPLICATION OF THEORY OF PLANNED BEHAVIOR ON THE INTEREST IN BUYING ORGANIC FERTILIZER WITH MOTIVATION AS AN INTERVENING VARIABLE IN THE CONTEXT OF SUSTAINABLE AGRICULTURE - Salehuddin, Salehuddin; Setyowati , Trias; Hermawan , Haris (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze farmer behavior through the application of the Theory of Planned Behavior on the interest in buying organic fertilizer, with motivation as an intervening variable in the context of sustainable agriculture. Method: This research was conducted using a quantitative research method. The number of samples was determined through a purposive sampling method, resulting in a total of 100 farmers in Banyuwangi Regency. Results: The results indicate that behavioral attitudes and subjective norms do not directly affect the interest in buying organic fertilizer. However, behavioral control and motivation have a direct influence on the interest in buying organic fertilizer. Indirectly, motivation mediates the relationship between behavioral attitudes and behavioral control with the interest in buying organic fertilizer, but it does not mediate the effect of subjective norms on the interest in buying organic fertilizer. Novelty: This study provides insights into the role of motivation in mediating the relationship between behavioral factors and the interest in buying organic fertilizer. Additionally, the findings highlight the importance of government support in encouraging and motivating young farmers to improve sustainable agricultural practices.